Sentinel node biopsy for skin melanoma - Kovačević Predrag; Višnjić Milan; Vlajković Marina; Kovačević Tatjana; Višnjić Aleksandar (Vojnosanitetski Pregled)
Background/Aim. Skin melanoma is one of the most malignant diseases with increasing incidence rate. Sentinel node biopsy (SNB) is very important for early detection of metastatic spread. The aim of the study was to analyze the first 40 patients with skin melanoma of 1 to 4 mm Breslow thickness when SNB was indicated. Methods. The patient characteristics, localization of the primary melanoma as well as histology grade were analyzed. SNB with intraoperative radiocolloid and methylene blue dye detection was performed. Results. Complication rate after SNB was analyzed and seroma was found in 5% of the patients. The therapeutic node dissection was performed in 10 patients with positive sentinel biopsy. The follow-up lasted two years. In five patients the false negative SNB was defined after the mean time of 11 months and the therapeutic dissection was performed. Conclusion. SNB in melanoma patients is a useful diagnostic procedure. It is advised for melanoma of 1 to 4 mm Breslow thickness.